2015
DOI: 10.1111/kykl.12073
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and Underperformance in Competitive Environments: Evidence from the National Hockey League

Abstract: Summary We find evidence of suboptimal decisions leading to underperformance in a policy experiment where two teams of professionals compete in a tournament (National Hockey League shootout) performing a task (penalty shot) sequentially. Before an exogenous policy change, home teams had to perform the task second in the sequence. After the policy change, home teams were given the choice to lead or to follow in the sequence. Home teams should move first only when this is optimal, and this should lead them to wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…For example, penalty shots in National Hockey League (NHL) shoot-outs are converted at a rate of approximately .33 per data published by the NHL. In a recent study of NHL shoot-outs, Kolev, Pina, and Todeschini (2015) found no evidence of FMA. Given the lower conversion rates of hockey penalty shots, this finding could be due to the reduced magnitude of FMA.…”
Section: Discussionmentioning
confidence: 91%
“…For example, penalty shots in National Hockey League (NHL) shoot-outs are converted at a rate of approximately .33 per data published by the NHL. In a recent study of NHL shoot-outs, Kolev, Pina, and Todeschini (2015) found no evidence of FMA. Given the lower conversion rates of hockey penalty shots, this finding could be due to the reduced magnitude of FMA.…”
Section: Discussionmentioning
confidence: 91%
“…The world of sports also provides many forums with which to test the impact of a tournament setting on performance. Previous studies have found evidence that pressure affects performance in soccer (Apesteguia & Palacios-Huerta, 2010; Dohmen, 2008), basketball (Cao, Price, & Stone, 2011; Deutscher, Frick, & Prinz, 2013; Toma, 2015), hockey (Depken, Sonora, & Wilson, 2012; Kolev, Pina, & Todeschini, 2015), tennis (González-Díaz, Gossner, & Rogers, 2012), and golf (Clark, 2002a, 2002b, 2007; Hickman & Metz, 2015; Hill, Hanton, Matthews, & Fleming, 2010; Wells & Skowronski, 2012; Wright et al, 1991). 1…”
mentioning
confidence: 99%
“…I show that players' performance at chess, for moderate levels of expertise onwards, also follows a Pareto distribution. Finally, this investigation is related to the literature that uses sports data to analyze an economic phenomena, as Kolev et al () who analyze whether agents act rationally using data on NHL games, or Schön et al () who analyze which managers put more effort into the firm, using golf handicaps data. Avsar and Unal () analyze whether an sport event, the FIFA World Cup, has a positive effect on trade; other papers, such as Torgler () and Bakkenbüll and Kiefer () analyze the factors that determine success in sports, such as football and tennis respectively.…”
Section: Related Literaturementioning
confidence: 99%